Accountants’ Perception to Increase the Usefulness of Agriculture Financial Accounting Information in Indonesia - Pirmansyah, Pirmansyah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study is to research how description attitudes and roles of accountants, understanding of agricultural financial information services in Indonesia to be improved from an accountant's perspective and accounting arrangements which include recognition, measurement, and disclosure of agricultural activities in accordance with PSAK 69 about agricultural accounting.